Economic mechanisms for SME development in Ukraine under EU financial support - Moshchych, Svitlana; Chernenko, Olha; Holub, Nataliia; Yakovyshyn, Yaroslav; Slipko-Kryvutsa, Dmytro; Голуб, Наталя Олександрівна; Яковишин, Ярослав Володимирович; Сліпко-Кривуца, Дмитро Ігорович (Mexico : IMEF, 2026)
EN: The study aims to develop a conceptual framework for SME development for supporting the development of small and medium-sized enterprises (SME) in Ukraine, particularly during wartime, through the integration of EU financial mechanisms. A mixed-method approach was used, combining comparative legal analysis of EU and Ukrainian practices with empirical assessment of SME needs and limitations. The core findings highlight a significant gap between existing Ukrainian support mechanisms and European standards, as well as a misalignment in policy implementation. The proposed model introduces a dynamic system of SME financial support tailored to different business development stages, emphasizing low-interest loans, co-financing, and innovation-driven incubators. Recommendations include adapting EU financial instruments, strengthening institutional readiness of SME, and promoting cross sectoral cooperation. The study acknowledges limitations due to wartime economic instability and inconsistent data across regions. Its originality lies in proposing a flexible, adaptive model grounded in both EU experience and local constraints. The findings contribute to the broader discourse on post-war economic resilience and policy innovation, offering a roadmap for enhancing the competitiveness and sustainability of SME in Ukraine.
Keywords: deregulation of small entrepreneurship; EU grant loans; financial support; grants; small business activity index; дерегуляція; малий бізнес; кредити; субсидовані ЄС; фінансова підтримка; гранти; рівень активності малого бізнесу